Wheat endosperm-specific transcription factor TaDOF6 enhances grain development by regulating TaSWEET13h expression and facilitating sugar and gibberellin transport - Ding, Run; Xiao, Tongtong; Li, ShaSha; Qiang, Jian; Zhang, Heng; Chang, Hongmiao; Yan, Yueming; Li, Xiaohui (Frontiers in Plant Science, 2025)
Seed size is regulated by the coordinated growth of the seed coat, embryo, and endosperm, and is modulated by multiple factors. Plant hormones, sugars, and cell cycle-related processes play key roles in this regulation. In this study, we demonstrate that overexpressing the endosperm-specific DOF transcription factor gene TaDOF6 significantly enhances the accumulation of sugars and gibberellin (GA3) in grains during the grain-filling stage. RNA sequencing (RNA-seq), quantitative real-time PCR (RT-qPCR), yeast one-hybrid (Y1H), electrophoresis mobility shift assay (EMSA), and dual-luciferase assays further confirmed that TaSWEET13h is a direct downstream target of TaDOF6. Structural and functional analyses identified TaSWEET13h as a multifunctional cell membrane-localized transporter that transports diverse soluble sugars and GA3. Notably, molecular dynamics (MD) simulations and in vitro assays revealed that hydrophobic interactions among non-polar amino acids primarily drive the transport of sucrose and GA3. Therefore, these findings elucidate the genetic regulatory network involving SWEET sugar transporters in grain size control and highlight promising targets for high-yield wheat breeding.